Paper, Perception and…Facts? Exploring Archaeological Heritage Management in the Mediterranean and the Weight of Public Archaeology - Almansa-Sánchez, Jaime (Ex Novo: Journal of Archaeology, 2021)
#pubarchMED is a project aiming to define the dynamics of archaeological heritage management in the Mediterranean from the perspective of public archaeology. Its ethnographic approach draws on three main sources: legal and academic literature, observation and the perception of professionals. This paper aims to delve into the development of public archaeology and how it impacts practice across the Mediterranean. While the importance of contemporary society for archaeologists seems to be high in the interviews conducted, it will be discussed to what level current practice actually deals with these issues in a critique of a traditional approach to archaeology that does not recognize the transversality of public archaeology or its importance for the future of the discipline itself.